Aetiology and potential animal exposure in central nervous system infections in Vietnam - Brindle, HE; Nadjm, B; Choisy, M; Thwaites, GE; van Doorn, HR (Springer, 2022)
An estimated 73% of emerging infections are zoonotic in origin, with animal contact and encroachment on their habitats increasing the risk of spill-over events. In Vietnam, close exposure to a wide range of animals and animal products can lead to acquisition of zoonotic pathogens, a number of which cause central nervous system (CNS) infections. However, studies show the aetiology of CNS infections remains unknown in around half of cases. We used samples and data from hospitalised patients with CNS infections, enrolled into the Vietnam Initiative on Zoonotic Infections multicentre study, to determine the association between aetiology and animal contact including those in whom the cause was unknown. Among 933 patients, a pathogen or an antibody response to it was identified in 291 (31.2%, 95% CI 28.3–34.3%). The most common pathogens were Streptococcus suis (n = 91 (9.8%, 8.0–11.9%)) and Japanese encephalitis virus (JEV) (n  = 72 (7.7%, 6.1–9.7%)). Commonly reported animal contact included keeping, raising or handling (n  = 364 (39.0%, 35.9–42.2%)) and handling, cooking or consuming raw meat, blood or viscera in the 2 weeks prior to symptom onset (n  = 371 (39.8%, 36.6–43.0%)), with the latter most commonly from pigs (n  = 343 (36.9%, 33.8–40.1%). There was no association between an unknown aetiology and exposure to animals in a multivariate logistic regression. Further testing for unknown or undetected pathogens may increase diagnostic yield, however, given the high proportion of zoonotic pathogens and the presence of risk factors, increasing public awareness about zoonoses and preventive measures can be considered.